NEW CONCEPTUAL APPROACH TOWARDS SELECTING THE BEST EDUCATIONAL PROGRAMMES - Victor A. Bolotov; Galina N. Motova; Vladimir G. Navodnov; Olga E. Ryzhakova (Высшее образование в России)
The article addresses the issues concerning the development of the public information system about the quality of education in the country. It also considers an approach towards creation of the monitoring system of the quality of educational process of a higher education institution based on an independent assessment of educational programmes, and includes objectives, tasks and principles of functioning and major indicators of this approach.